Detection of X‐Ray Doses with Color‐Changing Hackmanites: Mechanism and Application. Issue 20 (19th July 2021) - Vuori, Sami; Colinet, Pauline; Norrbo, Isabella; Steininger, Ralph; Saarinen, Timo; Palonen, Heikki; Paturi, Petriina; Rodrigues, Lucas C. V.; Göttlicher, Jörg; Le Bahers, Tangui; Lastusaari, Mika
Abstract: Hackmanites, a variety of sodalite with the general formula Na8 Al6 Si6 O24 (Cl, S)2, are a family of nature‐based smart materials having the ability for reversible photochromism upon UV or X‐ray exposure. Being nontoxic, cheap, and durable, hackmanite would be an optimal material for the visual detection of the presence of X‐rays in simple portable systems. However, its X‐ray‐induced coloring abilities are so far known only qualitatively. In this work, a combination of experimental and computational methods is used to reveal the mechanism of X‐ray‐induced color changing in these materials. Finally, their use is demonstrated both in color intensity‐based X‐ray dosimetry and photochromic X‐ray imaging. Abstract : Hackmanites are smart materials having the ability for reversible photochromism upon X‐ray exposure. They are highly promising for visualizing X‐rays in a simple and portable way. With a comprehensive combination of experimental and computational tools, the mechanism behind X‐ray‐induced photochromism in hackmanites is revealed. Then, it is shown how they can be applied in dosimetry and easy photochromic imaging.